$- frac 3 4 left(- frac 1 3 right)=$
- $- frac 3 4 + left (- frac 1 3 right )=$
- Find $ frac 1 2 left ( frac 3 4 right 3$
- Frac 3 4 - left (- frac 1 6 right
- $ frac 15 4 + left (- 4 frac 1 3 right )=$
- Frac 3 4 left 2x 16 right )= frac 1 3 left x 6 right
- $ frac 3 4 left 8g - frac 1 4 - frac 2 3 g right )=$
- Frac 1 2r 3 3 left 4 - frac 3 2r right
- Frac 1 2r 3 3 left 4 frac 3 2r right answer
- $1 frac 3 5 cdot left (- 3 frac 3 4 right )=$
- Вычислите left ( frac 1 x^ 3 right ) '
- Обчисліть left ( frac 1 3 right )^ -7 cdot left ( frac 1 3 right )^ 5